2014
DOI: 10.1161/jaha.114.000983
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term Changes in Ambient Particulate Matter and Risk of Stroke: A Systematic Review and Meta‐analysis

Abstract: BackgroundStroke is a leading cause of death and long‐term disability in the United States. There is a well‐documented association between ambient particulate matter air pollution (PM) and cardiovascular disease morbidity and mortality. Given the pathophysiologic mechanisms of these effects, short‐term elevations in PM may also increase the risk of ischemic and/or hemorrhagic stroke morbidity and mortality, but the evidence has not been systematically reviewed.Methods and ResultsWe provide a comprehensive revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 86 publications
(211 reference statements)
3
78
2
2
Order By: Relevance
“…However, direct evidence on the association between PM 2.5 and ischemic stroke was limited and the findings remain equivocal. A comprehensive review identified only six studies published before January 2014 that specifically examined the association between short-term exposure to PM 2.5 and the risk of ischemic stroke hospitalization, and the pooled results suggested a non-significant increased risk of hospital admission for ischemic stroke per 10 μg/m 3 increase in PM 2.5 30 . Wellenius et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, direct evidence on the association between PM 2.5 and ischemic stroke was limited and the findings remain equivocal. A comprehensive review identified only six studies published before January 2014 that specifically examined the association between short-term exposure to PM 2.5 and the risk of ischemic stroke hospitalization, and the pooled results suggested a non-significant increased risk of hospital admission for ischemic stroke per 10 μg/m 3 increase in PM 2.5 30 . Wellenius et al .…”
Section: Discussionmentioning
confidence: 99%
“…[50] Additional inconsistencies and non-significant associations are documented for analyses examining hospital admissions of certain stroke sub-types. [51] While greater caution should be exercised when interpreting these conclusions, they may prove informative for future studies. A 2014 meta-analysis including 34 studies examined the transient effects of air pollution.…”
Section: Air Pollution and Strokementioning
confidence: 99%
“…This research directly addressed gaps in the research calling for large studies that specifically examined ischemic and hemorrhagic stroke as well as used medical-record review for event ascertainment. 33 We have provided strong evidence of a lack of association.…”
Section: Discussionmentioning
confidence: 75%